Child protection practice - Ferguson, Harry (Thomas Harold) (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"When it comes to child protection, who is showing social workers exactly what they should be doing? In this book, Harry Ferguson guides you through the day-to-day realities of child protection practice, outlining its deep complexities along with the knowledge, skills, values and organizational supports necessary to do this difficult job"--
Machine generated contents note: -- Introduction: child protection practice -- Knocking on the door of history: the emergence of child protection practice -- Child abuse and the development (and decline) of intimate child protection practice -- Streets, housing estates, doorsteps: getting to the child -- The home visit: houses and the struggle to protect the abused child -- The reverberations of home visiting: going into the depths to protect children -- Hospitals, office interviews and the emotional complexity of practice -- Working with children in child protection -- The importance of touch in child protection -- Working with fathers -- Working with mothers -- Culturally sensitive child protection practice -- Multi-agency working -- Good authority and working with hostile and deceptive adults and overcoming resistance -- Spaces for reflection 1: the car in child protection -- Spaces for reflection 2: supervision and organisational practices that promote good child protection -- Conclusion: intimate child protection practice.
Includes bibliographical references and index.
Keywords: Child abuse -- Prevention; Social work with children